2022
DOI: 10.1002/adma.202202869
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Induced Melting and Solvation Reconfiguration of Phase‐Change Electrolyte

Abstract: Phase‐change materials (PCMs) are a unique and exciting class of materials with bright prospects in wide‐ranging sustainable technologies such as thermal and electrochemical energy storage. While impressive, the effect of gaseous species on PCMs remains largely unexplored hitherto. Here, a gaseous co‐solvent is reported that can facilitate melting and modulate physical properties such as viscosity and ion conduction of PCMs. Especially for the appealing application of PCMs as electrolytes, gaseous species also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The addition of @LCKB lithium replenishment material results in a decrease of C–O and C=O content and increased LiF content in the SEI film at the anode surface (Figure (b,d)). It is reported that CO 2 , the decomposition product of lithium carbonate, can be dissolved in the electrolyte solution and modifies the fundamental electrochemical process . In detail, the dissolved carbon dioxide limits involvement of the electrolyte solvent in the lithium-ion solvation process and enhances interactions between the solvated lithium ion and anion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of @LCKB lithium replenishment material results in a decrease of C–O and C=O content and increased LiF content in the SEI film at the anode surface (Figure (b,d)). It is reported that CO 2 , the decomposition product of lithium carbonate, can be dissolved in the electrolyte solution and modifies the fundamental electrochemical process . In detail, the dissolved carbon dioxide limits involvement of the electrolyte solvent in the lithium-ion solvation process and enhances interactions between the solvated lithium ion and anion.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that carbon dioxide dissolved in the electrolyte solution is capable of promoting formation of LiF in the SEI. , On one hand, carbon dioxide limits participation of the electrolyte solvent in the lithium-ion solvation process, which suppresses electrolyte solvent decomposition and decreases organic content in the SEI layer. On the other hand, carbon dioxide enhances the interactions between the solvated lithium cation and anion, leading to enhanced decomposition of the anion to generate LiF species . As a result, the formation of LiF in the SEI layer is promoted.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the molecular conformation and intra/intermolecular interactions in different solution environments were analyzed by the characteristic distance of the radial distribution functions (RDFs). And the coordination number ( CN ) was further calculated with eq C N = prefix∑ 0 r 4 π r 2 ρ g false( r false) δ r where r is the radius, ρ is the atomic density, g ( r ) represents the radial distribution functions, and δr is the sampling interval . In fact, the coordination numbers for the oxygen atoms of methanol and acetone were calculated separately, and the total coordination number of the solutes was further obtained by summing them.…”
Section: Methodsmentioning
confidence: 99%
“…This depends on the electrolyte/electrode interface chemistry and further relies on the solvation structure of the electrolyte. 31 In the solvation structure, the Li + -solvated sheath has a higher probability of approaching the electrode than free solvents/ anions, thus contributing to the main components of SEI. 32 We further analyzed the effect of temperature (HT and RT) on the Li + -solvation structure of the S10F1 electrolyte by molecular dynamics (MD) simulations.…”
Section: Formation and Characterizations Of The Scl-deesmentioning
confidence: 99%
“…Except for physical properties, the chemical/electrochemical stability of the electrolyte toward electrodes is critical, especially for the high-temperature application. This depends on the electrolyte/electrode interface chemistry and further relies on the solvation structure of the electrolyte 31. In the solvation structure, the Li + -solvated sheath has a higher probability of approaching the electrode than free solvents/ anions, thus contributing to the main components of SEI 32.…”
mentioning
confidence: 99%